2020
DOI: 10.1186/s13568-020-01034-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a species-specific aminotransferase in Pediococcus acidilactici capable of forming α-aminobutyrate

Abstract: During cheese ripening, the bacterial strain Pediococcus acidilactici FAM18098 produces the non-proteinogenic amino acid, α-aminobutyrate (AABA). The metabolic processes that lead to the biosynthesis of this compound are unknown. In this study, 10 P. acidilactici, including FAM18098 and nine Pediococcus pentosaceus strains, were screened for their ability to produce AABA. All P. acidilactici strains produced AABA, whereas the P. pentosaceus strains did not. The genomes of the pediococcal strains were sequenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…3 , S3 and S4 ). AABA has a similar structure to that as Ala, and other ATs that were able to use Leu, Ala, Met, and Phe are also able to use AABA as an amino donor ( 41 ). This finding also demonstrates that the easily scalable nature of the oxime MS assay enables detection of novel AT activity and also provides rich experimental data to facilitate structure–function analyses of the AT enzyme family.…”
Section: Discussionmentioning
confidence: 99%
“…3 , S3 and S4 ). AABA has a similar structure to that as Ala, and other ATs that were able to use Leu, Ala, Met, and Phe are also able to use AABA as an amino donor ( 41 ). This finding also demonstrates that the easily scalable nature of the oxime MS assay enables detection of novel AT activity and also provides rich experimental data to facilitate structure–function analyses of the AT enzyme family.…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds, PLA and HPLA, exhibit antifungal activity (Lavermicocca et al, 2000). Additionally, it possesses the genes of the arginine deiminase pathway, which converts arginine to ornithine (Eugster et al, 2019;Wenger et al, 2020). This metabolic pathway releases carbon dioxide which could influence the eye formation in cheese.…”
Section: Introductionmentioning
confidence: 99%
“…This metabolic pathway releases carbon dioxide which could influence the eye formation in cheese. Finally, P. acidilactici can degrade serine and threonine and, in turn, form alanine and α-aminobutyric acid in medium and cheese (Eugster et al, 2019;Wenger et al, 2020). We assume that serine and threonine are converted to alanine and α-aminobutyric acid, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently to the pursuit of these objectives, the Agroscope strain collections was to be characterised using HTS to identify their potential and enable their targeted use in agriculture and food sectors. The project was able to analyse bacterial species involved in cheese ripening (Moser et al, 2018;Wenger et al, 2020), study fungal biological control agents to control pest arthropods (Mayerhofer et al, 2019;Fernández-Bravo et al, 2021), and detect and characterise insect (Pedrazzini et al, 2021) and nematode (Koutsovoulos et al, 2020) The present document has been produced and adopted by the bodies identified above as author(s). In accordance with Article 36 of Regulation (EC) No 178/2002, this task has been carried out exclusively by the author(s) in the context of a grant agreement between the European Food Safety Authority and the author(s).…”
mentioning
confidence: 99%